Technical Note: Scintillation well counters and particle counting digital autoradiography devices can be used to detect activities associated with genomic profiling adequacy of biopsy specimens obtained after a low activity 18F‐FDG injection. Issue 5 (23rd March 2018) - Kirov, Assen S.; Fanchon, Louise M.; Seiter, Daniel; Czmielewski, Christian; Russell, James; Dogan, Snjezana; Carlin, Sean; Pinker‐Domenig, Katja; Yorke, Ellen; Schmidtlein, C. Ross; Boyko, Vitaly; Fujisawa, Sho; et al.
Abstract : Purpose: Genomic profiling of biopsied tissue is the basis for precision cancer therapy. However, biopsied materials may not contain sufficient amounts of tumor deoxyribonucleonic acid needed for the analysis. We propose a method to determine the adequacy of specimens for performing genomic profiling by quantifying their metabolic activity. Methods: We estimated the average density of tumor cells in biopsy specimens needed to successfully perform genomic analysis following the Memorial Sloan Kettering Integrated Mutation Profiling of Actionable Cancer Targets (MSK‐IMPACT) protocol from the minimum amount of deoxyribonucleonic acid needed and the volume of tissue typically used for analysis. The average 18 F‐FDG uptake per cell was assessed by incubating HT‐29 adenocarcinoma tumor cells in 18 F‐FDG containing solution and then measuring their activity with a scintillation well counter. Consequently, we evaluated the response of two devices around the minimum expected activities which would indicate genomic profiling adequacy of biopsy specimens obtained under 18 F‐FDG PET/CT guidance. Surrogate samples obtained using 18G core needle biopsies of gels containing either 18 F‐FDG‐loaded cells in the expected concentrations or the corresponding activity were measured using autoradiography and a scintillation well counter. Autoradiography was performed using a CCD‐based device with real‐time image display as well as with digital autoradiography imaging plates following a 30‐min off‐line protocol for specimen activity determination against previously established calibration. Results: Cell incubation experiments and estimates obtained from quantitative autoradiography of biopsy specimens (QABS) indicate that specimens acquired under 18 F‐FDG PET/CT guidance that contained the minimum amount of cells needed for genomic profiling would have an average activity concentration in the range of about 3 to about 9 kBq/mL. When exposed to specimens with similar activity concentration, both a CCD‐based autoradiography device and a scintillation well counter produced signals with sufficient signal‐to‐background ratio for specimen genomic adequacy identification in less than 10 min, which is short enough to allow procedure guidance. Conclusion: Scintillation well counter measurements and CCD‐based autoradiography have adequate sensitivity to detect the tumor burden needed for genomic profiling during 18 F‐FDG PET/CT‐guided 18G core needle biopsies of liver adenocarcinoma metastases.